Avenue of spies : a true story of terror, espionage, and one American family's heroic resistance in Nazi-occupied France - Kershaw, Alex (Crown Publishers, 2015)
Brings to life the true story of an American doctor and his family in Paris, and his heroic espionage efforts during World War II. Exclusive Avenue Foch was Paris's hotbed of spies, secret police, informers, and Vichy collaborators. So when the couple at number 11-- American physician Sumner Jackson and his Swiss-born wife Toquette-- joined the French Resistance, they knew the stakes were extraordinarily high. They would be risking not only their own lives but that of their only child, twelve-year-old Phillip. There was no more dangerous place in all of Occupied Europe than their street-- Nazis had commandeered almost every building. At number 31 was the "mad sadist" Theodor Dannecker, charged with deporting French Jews to concentration camps. Number 72 housed the Parisian headquarters of the Gestapo. As their Nazi neighbors rounded up Jews and ruthlessly destroyed all opposition, the Jacksons stepped up their own private war against Hitler. From the American Hospital, Sumner smuggled fallen Allied crewmen out of France. And Toquette agreed to allow the Goélette network of the Resistance to use their home as a drop box for vital information en route to Britain. As D-Day neared, the noose began to tighten; when the family's secret was finally discovered, they were sent on a journey into the black heart of the war-torn continent from which there was little chance of return. Drawing upon a wealth of primary source material and extensive interviews with Phillip Jackson, Alex Kershaw re-creates the City of Light during its darkest days.--Adapted from book jacket.